The geography of war and peace : from death camps to diplomats - Flint, Colin, 1965- (OUP E-Books., 2005)
How and why war and peace occur cannot be understood without realizing that those who make war and peace must negotiate a complex world political map of sovereign spaces, borders, networks, and scales. This book takes advantage of a diversity of perspectives as it analyzes the political processes of war and their spatial expression.